Development of Information Service Modul to Enhance Meaning of Life: A Study on Minangkabau Adolescents - Yuli Permatasari; Herman Nirwana; Hanifah Usman (Universitas Ahmad Dahlan, 2024)
This study examined the development of informational service materials aimed at enhancing the meaning of life among Minangkabau ethnic students in secondary schools.